Challenges of minimally invasive distal pancreatectomy: whether to preserve or not the spleen and splenic vessel - Dumitrascu, Traian (Laparoscopic Surgery, 2018)
I appreciate so much the invitation to comment on the article of Nakata and co-workers (1). In this systematic review and meta-analysis are comparatively assessed the outcomes of minimally invasive distal pancreatectomy, with and without spleen preservation (1). Furthermore, in the subgroup of patients with spleen preservation, the outcomes of splenic vessel preservation technique were compared to those of the technique in which the splenic artery and vein are resected (1).